Factors Affecting Traumatic Brain Injury Outcome Among Patients Treated for Head Injury at Surgical Side, in Nekemte Referral Hospital, Oromia, Ethiopia. - Mitiku Getachew Kumara; Miresa Banti Dhugasa (Journal of Spine and Neuroscience, 2020)
Background Traumatic brain injury is an expanding major public health problem and the leading cause of death of the young and productive part of the world’s population. Research is mainly done in high-income countries where only a small proportion of the worldwide fatalities occur. Only few studies have examined prognostic factors of traumatic brain injury outcome in developing countries including Ethiopia. This study was aimed at defining the peculiar demographic and other associated factors of traumatic brain injury (TBI) outcome among patients treated for head injury at Nekemte Referral Hospital. Objective The main purpose of this study was to describe the magnitude of TBI outcome and assess factors associated with unfavourable outcome of TBI among patients treated for head injury at the surgical side in Nekemte Referral Hospital from July 8, 2016 to July 7, 2018. Methods A retrospective cross-sectional document review was conducted among TBI patients treated for head injury from July 8, 2016 to July 7, 2018 at Nekemte Referral Hospital. Data were collected using a pre-tested data collection format. Data analysis was done using SPSS version 20. Descriptive statistics were computed and association between the dependent and independent variables were assessed by using logistic regression. Odds ratios with 95% confidence interval were computed. Significant association was declared when the p value was <0.05. Results In this study, out of 378 cases 95 (25.1%) were discharged with unfavourable outcome of which 37(9.8%) were neurologic deficits and 58 were deaths giving overall mortality rate of 15.3%. Patient age>60years (AOR: 15.13; 95%CI: 3.575-64.028), time interval from injury to treatment (AOR: 16.054; 95%CI: 5.832-44.194), low GCS (AOR: 18.224; 95%CI: 4.167, 79.695), conservative management (AOR: 20.774; 95%CI: 6.106-70.681), pupils abnormality (AOR: 9.078; 95%CI: AOR: 2.996-27.509) were associated with unfavourable outcome. Conclusions A quarter of patients treated for TBI at Nekemte Referral Hospital are discharged with unfavourable outcomes. Old age, delayed presentation to the hospital, low GCS, conservative management, and pupillary abnormality increase the odds of unfavourable outcome. Timely management of TBI before patients develop secondary brain injury and use of surgical intervention based on CT scan diagnosis will reduce the occurrence of unfavourable outcome.
Keywords: Traumatic Brain Injury